Comparison of different models of W' balance in high-level road cycling races - Millour, G.; Lajoie, C.; Domingue, F. (International Journal of Performance Analysis in Sport, 2023)
This study aimed to compare different models of W' balance (W'bal) during road cycling races. These models allow tracking of the depletion and reconstitution of energy reserves during intermittent exercises. Fifteen high-level cyclists shared a year of data, including the power output and GPS records. They then selected a race during which they were in very good condition, and where they reached a maximum level of exhaustion in the final phase. Based on their seasonal data, their critical power and W' were calculated and incorporated into the integral and differential models of Skiba and Bartram model. W'bal was calculated throughout the races and normalised to W'. The integral, differential, and Bartram models predicted a mean W'bal of 41 ± 27%, 67 ± 17%, and 82 ± 9%, a minimum W'bal of -21 ± 28%, -3 ± 22%, and 22 ± 24%, and a W'bal at the identified point of exhaustion of 0 ± 30%, 21 ± 28%, and 42 ± 23% (all significantly different, p < 0.01). Given the large differences between the models and the high inter-individual variability of W'bal at the participant-identified point of exhaustion, this study shows that the models are not interchangeable and that the values of W'bal should be considered with caution when analysing races.